A qualitative study of nurses' experiences of self-care counseling in migrant patients with heart failure - Harshida Patel; Grazyna Szkinc-Olsson; Madeleine Lennartsson Al Liddawi (Elsevier, 2021)
Objectives: This study aims to enhance researchers' and nurses' understanding of how to best support migrant patients with heart failure in self-care management. Previous research on self-care in heart failure patients has highlighted its importance, particularly among migrant populations. Nurses play an important role in informing and engaging patients with chronic conditions like heart failure to support their active participation in self-care. However, nurses' experiences of providing self-care counseling to migrant populations with heart failure have not been studied. Methods: A qualitative study was conducted. Nurses working with migrant patients with HF (n = 13) from different types of facility in Western Sweden were interviewed between October and December 2020. Data were collected using semi-structured interviews and analyzed using inductive thematic analysis. Results: The main theme that emerged from the interviews was the difficulty for nurses "to find balance" in self-care counseling. The nurses during self-care counseling had: "to accept challenges," "to use creative strategies," faced "problems related to health literacy," and "to work according to their (the nurses') obligations." It was evident that nurses faced several challenges in counseling migrants in self-care, including language and cultural barriers, time resource constraints, low levels of health literacy, and experienced disharmony between the law and their professional norms. They perceived building caring relationships with their patients to be crucial to fostering health-promoting self-care processes. Conclusions: To increase self-care adherence, nurses must become more sensitive to cultural differences and adapt self-care counseling to patients' health literacy. The findings of this research support and challenge nurses in providing the best counsel to migrant patients with heart failure living in Sweden's multi-ethnic society. Policymakers in the health care organization should act to facilitate mutual cultural understanding between all involved partners for patient-safe self-care counseling.